Systemic Racism and Racial Identity in Brit Bennett’s The Vanishing Half: Rasisme Sistemik dan Identitas Ras dalam The Vanishing Half karya Brit Bennett - Febrianto, Ibnu Dafa; Supsiadji, Mateus Rudi (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This article explores the representation of systemic racism in Brit Bennett’s novel The Vanishing Half, using Joe R. Feagin’s Systemic Racism Theory and a sociological approach to literature. The study analyzes how racism is portrayed not just as individual prejudice but as a multidimensional system embedded in institutions, cultural norms, and personal identity. The novel follows the diverging paths of twin sisters, Desiree and Stella, who make drastically different choices about their racial identities choices that influence their families across generations. Through textual analysis, the article identifies four key forms of racism depicted in the novel: structural, institutional, interpersonal, and internalized. Structural racism appears in the town of Mallard’s colorist ideology; institutional racism manifests in unequal education and employment; interpersonal racism is evident in microaggressions and exclusion; while internalized racism is portrayed through Stella’s rejection of her Black identity. The study reveals how these forms of racism shape the characters’ identities, relationships, and life opportunities. By combining literary analysis with sociological theory, the article argues that The Vanishing Half serves not only as a powerful narrative but also as a critique of enduring racial inequality in American society. It highlights literature’s role in exposing and resisting systemic oppression through storytelling.